Outcome Factors in Hypoxic Ischemic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The predictive value of history, examination, Glasgow Coma Scale (GCS) scores, EEG and sensory evoked potentials (SEP) in the prognosis of children with acute hypoxic-ischemic encephalopathy (HIE) was evaluated at the University Hospital of Lille, France.